Causes of construction reworks and their mitigation strategies - HAYAT, KAMRAN (2018)
Projects always having a limited time period and each of them are versatile in concept. With due regards especially construction sector facing a difficulties facing many problems but one of the major is rework. This all is due to limitless requirements and unforeseen circumstances. Therefore this project management dissertation is about digging deep causes of project reworks as well as its mitigation ways consisting of literature review which ends up with conceptual model and developed 5 hypothesis which is core of my survey questionnaire. Its factors mainly includes reasons of project works repetitions are poor project managements , un maintained project machinery and less manpower , countries overall surround situations, project design confusions , stakeholder concerns and week communication plans. On the opposite side reworks mitigation plan consists of better quality assurance/control methods, better condition project machines and efficient staff and professional workers, owner demand oriented, and better communications procedures. These hypothesis conclusions made on SPSS results whose base is professionals reply on questionnaire. Later 3 project reworks records goggled from my professional history , meetings done with management’s team about the problems faced due to reworks on projects.3 reworks case studies discussed in tabular from and shown their results in terms of effects of project schedule, project cost, and project quality in graphical representation. Further going forward hypothesis results and case studies comparison discussed which concluded that literature review, SPSS results and case studies are totally aligned about route causes and further mitigation techniques. Later writer highlighted strategy planning approach and reduction of reworks by performance management techniques, reworks risk considerations and lately dissertation recommended to build an innovative teams on the project which is the only way of reducing the reworks on the projects. Survey questionnaire prepared considering the literature review on project reworks and its mitigation strategies further considering views of market professionals. SPSS used to analysis the professional feedback and 3 project case studies tabulated after extensive interviews. Going further comparison done between SPSS analysis and 3 case studies. Lastly highlights done on strategy and building innovative team which reduces project reworks. This dissertation shown six causes of reworks and five mitigation techniques to reduce the reworks. Main causes of works reputation are poor project management team, less manpower and non-maintained construction machinery, country political situation, Week project documents, stakeholders and communication problems and weak commination between project team. In mitigation techniques consists of best quality control procedures, competent staff and skilled workers, Owner demand focused, reviewing the project documents and controlled communication. Considering the above objective conceptual model prepared following the questionnaire. Later these factors will be analyzed to computer the significance and variance of independent factors on depend factors. By reducing the reworks , client feel more comfortable and satisfied, company market value increases ,less wastage of material, reduce waste and time, fatigue and tension will be less among staff , more comfortable and safe work environment can be achieved. SPSS results on professional feedback re confirmed that above stated causes from literature review prompts the works repetition on the project and stated above mitigation strategies reduces the reworks dramatically which controls project cost and schedule. Positive variance achieved by seeing regression results, the highest variance noted 28.6 % by implementing by applying global factors. Further R square results show that implementation of QA/QC principles added maximum variance which is 27.9 percent to improve project management which reduces the reworks. Going further deep in practical life all 3 cases studies reworks caused due to above highlighted discrepancies on the project which really caused project completion over cost and over schedule. he student has not find opportunity working long time in building industry so no that deep technical details in this desertion about causes of reworks in building construction works and their resolutions .This assignment is only covering infrastructure part of civil works around gulf but mostly in UAE. This dissertations will guide infrastructure managers to achieve project milestones and key performance indicators by keeping in mind works end results .This dissertations is one among value addition in current project management library. Finally it really a useful guide for managers to keep project on schedule and on track especially at difficult times. The writer wishes that due to unlimited complications in construction industry manager shall always keep in mind that with in no time project may enter into works repetition stage which would be enough loosing owner trust. So professionals to discover the strategies to complete on schedule and on cost project by reducing projects reworks.